Gene Expression Analysis Suggests Immunological Changes of Peripheral Blood Monocytes in the Progression of Patients With Coronary Artery Disease - Wang, Chunyue; Song, Chenxi; Liu, Qianqian; Zhang, Rui; Fu, Rui; Wang, Hao; Yin, Dong; Song, Weihua; Zhang, Haitao; Dou, Kefei (Frontiers in Genetics, 2021)
Objectives: To analyze the gene expression profile of peripheral blood monocytes in different stages of coronary artery disease (CAD) by transcriptome sequencing, and to explore potential genes and pathway involved in CAD pathogenesis. Methods: According to the screening of coronary angiography and quality control of blood samples, 8 intermediate coronary lesion patients were selected, then 8 patients with acute myocardial infarction and 8 patients with normal coronary angiography were matched by age and gender. Transcriptomics sequencing was conducted for the peripheral blood monocytes of these 24 samples by using Illumina HiSeq high-throughput platform. Then differentially expressed genes (DEGs) were analyzed. Gene Ontology (GO) functional annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway annotation and protein-protein interaction (PPI) network were applied to annotate the potential functions of DEGs. Results: Compared with normal coronary angiography group, we identified a total of 169 DEGs in the intermediate coronary lesion group, which were significantly enriched in 611 GO terms and 11 KEGG pathways. Compared with normal coronary angiography group, we found a total of 2028 DEGs, which were significantly enriched in 1,376 GO terms and 97 KEGG pathways in the acute myocardial infarction group. Compared with intermediate coronary lesion group, we found a total of 2376 DEGs in the acute myocardial infarction group, which were significantly enriched in 245 GO terms. The cross-comparison between normal versus intermediate coronary lesion group, and normal versus acute myocardial infarction group included 98 differential genes with 65 up regulated and 33 down regulated genes, which were significantly enriched in 489 GO terms and 2 KEGG pathways. During the progression of CAD, there was a significant up-regulated expression of CSF3、IL-1A、CCR7 and IL-18, and down-regulated expression of MAPK14. Besides GO items such as inflammatory response was significantly enriched, KEGG analysis showed the most remarkable enrichments in IL-17 signaling pathway and cytokine-cytokine receptor interactions. Conclusions: Transcriptomics profiles varies in patients with different severity of CAD. CSF3、IL-1A、CCR7、IL-18 and MAPK14, as well as IL-17 signaling pathway and cytokines and cytokine receptor interaction signaling pathway related with inflammatory response might be the potential biomarker and targets for the treatment of coronary artery disease.